Literary and Analytic Transformations of Trauma: Repetition, Revision and Rebirth in Two Stories of Raymond Carver - Halfon, Sibel; Weinstein, Lissa (Educational Publishing Foundation-American Psychological Assoc, 2016)
A linguistic analysis of two related short stories written by Raymond Carver, The Bath (1981) and A Small, Good Thing (1983), highlights the differences in their narration of the same traumatic event-the sudden death of a child. In The Bath, the monotony and repetition of the linguistic structures and the lack of descriptive nouns preserve the depicted trauma in its original raw form. In contrast, in A Small, Good Thing the emphasis on detailed descriptions, and the varied use of language transforms the brutally realistic trauma into a deeply moving and affectively rich experience. A parallel can be drawn to the psychoanalytic process, which aims to move the patient from fixed traumatic repetitions toward sublimated forms of representation within the transference. Adele Tutter (2009, 2011) has examined different versions of Carver's stories in relation to Carver's autobiography and discussed how he projected himself in the narrative. Building on Tutter's work, this article will attempt a systematic comparison of the language of these 2 stories, discussing the trajectory from traumatic repetitions to symbolization in psychoanalytic theory.
Keywords: Raymond Carver; Trauma; Repetition; Representation; Transference